Familiarity Bias pada Perkembangan UKM Srabi Ngampin Ambarawa - Rita Meiriyanti; Dhea Rizky Amelia (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2022)
The purpose of this study were: to determine the familiarity bias in the development of the srabi’s SMEs Ngampin Ambarawa. This study uses a qualitative method with a phenomenological approach. The sample used in this study were srabi traders who are members of the Mekar Lestari SMEs, in Ngampin Village Ambarawa. This study gives the result that familiarity is a consideration for consumers in making decisions. Familiarity causes consumers to choose products in terms of what they think and know and understand. So the scope of the decision is based solely on the judgment that the product is known in advance. The role of word of mouth communication and the power of referral is to provide knowledge about srabi products so that later consumers are familiar and have a good understanding. The CSR developed by srabi Ngampin has a positive reputation and image so that it becomes the main non-financial capital and added value for Srabi's SMEs to be able to grow in a sustainable manner (sustainable development).